2008
DOI: 10.1097/ico.0b013e31816ed54c
|View full text |Cite
|
Sign up to set email alerts
|

Light and Transmission Electronic Microscopy Evaluation of Lyophilized Corneas

Abstract: Lyophilization with sacarousis and rehydration with BSS may be a good method for anterior lamellar transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Degeneration of keratocytes with necrotic and apoptotic changes due to the dehydration process is expected. It has been observed with ultrastructural evaluation in dehydrated corneas after lyophilization or cryopreservation, with or without the use of a cryoprotective agent (10,23). For this reason, it was not necessary to include a control group to compare air-drying with other procedures for dehydrating corneal tissue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Degeneration of keratocytes with necrotic and apoptotic changes due to the dehydration process is expected. It has been observed with ultrastructural evaluation in dehydrated corneas after lyophilization or cryopreservation, with or without the use of a cryoprotective agent (10,23). For this reason, it was not necessary to include a control group to compare air-drying with other procedures for dehydrating corneal tissue.…”
Section: Discussionmentioning
confidence: 99%
“…The conventional preservation times of whole corneas and stromal lenticules can be lengthened by cryopreservation/vitrification (5), dehydration without freezing (6), glycerolization (7)(8)(9), lyophilization (or freeze-drying) (10)(11)(12), and sterilization by gamma irradiation (13).…”
Section: Introductionmentioning
confidence: 99%
“…Lyophilization is thought to optimize preservation of corneal architecture. Recent studies using light and transmission electron microscopy found that lyophilization preserved general corneal structure, parallelism of the collagen fibers, Bowman's layer and the epithelial basement membrane 1718. No comparative studies have yet determined if lyophilized and glycerol-dehydrated tissues exhibit ultrastructural differences following tissue rehydration and, if detected, to what extent these differences affect tissue quality and corneal transparency.…”
Section: Introductionmentioning
confidence: 99%